Pictogram Prediction in Alternative Communication Boards: a Mapping Study - Pereira, Jayr A.; Medeiros, Sheyla de; Zanchettin, Cleber; Fidalgo, Robson do N. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2022)
Alternative communication boards (ACB) are tools that try to compensate for the difficulties faced by people with complex communication needs. Generally, these tools consist of a mobile application in which the user can construct sentences by arranging pictograms (picture+label pair representing a concept) in sequence. This study systematically maps the literature on pictogram prediction in ACBs. We analyzed eight studies to investigate how computational methods are used for pictogram prediction, how these proposals are evaluated, and the studies' outcomes regarding user communication improvement. The main findings indicate the usage of different methods for pictogram prediction and a mixture of automatic and expert evaluation, which lead to inconclusive outcomes regarding user communication improvement.